Distinct fine‐root responses to precipitation changes in herbaceous and woody plants: a meta‐analysis. Issue 4 (19th November 2019) - Wang, Peng; Huang, Kailing; Hu, Shuijin
Summary: Precipitation is one of the most important factors that determine productivity of terrestrial ecosystems. Precipitation across the globe is predicted to change more intensively under future climate change scenarios, but the resulting impact on plant roots remains unclear. Based on 154 observations from experiments in which precipitation was manipulated in the field and root biomass was measured, we investigated responses in fine‐root biomass of herbaceous and woody plants to alterations in precipitation. We found that root biomass of herbaceous and woody plants responded differently to precipitation change. In particular, precipitation increase consistently enhanced fine‐root biomass of woody plants but had variable effects on herb roots in arid and semi‐arid ecosystems. In contrast, precipitation decrease reduced root biomass of herbaceous plants but not woody plants. In addition, with precipitation alteration, the magnitude of root responses was greater in dry areas than in wet areas. Together, these results indicate that herbaceous and woody plants have different rooting strategies to cope with altered precipitation regimes, particularly in water‐limited ecosystems. These findings suggest that root responses to precipitation change may critically influence root productivity and soil carbon dynamics under future climate change scenarios.